Local dynamic stability and variability of gait are associated with fall history in elderly subjects - Toebes, Marcel J.P.; Hoozemans, Marco J.M.; Furrer, Regula; Dekker, Joost; van Dieën, Jaap H. (Gait & posture, 2012)
► Gait variability is often used to assess fall risk in elderly subjects. ► Local dynamic stability may be an additional predictor of fall risk. ► Gait kinematics were measured in 134 healthy elderly subjects walking on a treadmill. ► Variability and local dynamic stability were, individually and combined, associated with fall history. ► Increased variability and decreased local dynamic stability are possible risk factors for falling. Gait parameters that can be measured with simple instrumentation may hold promise for identifying individuals at risk of falling. Increased variability of gait is associated with increased risk of falling, but research on additional parameters indicates that local dynamic stability (LDS) of gait may also be a predictor of fall risk. The objective of the present study was to assess the association between gait variability, LDS of gait and fall history in a large sample of elderly subjects. Subjects were recruited and tested at a large national fair. One hundred and thirty four elderly, aged 50–75, who were able to walk without aids on a treadmill, agreed to participate. After subjects walked on a treadmill, LDS (higher values indicate more instability) and variability parameters were calculated from accelerometer signals (trunk worn). Fall history was obtained by self-report of falls in the past 12 months. Gait variability and short-term LDS were, individually and combined, positively associated with fall history. In conclusion, both increased gait variability and increased short-term LDS are possible risk factors for falling in the elderly.